Identification of general coordination level according to laterality in handball - Badau, D. (3rd International Scientific Conference: Exercise and quality of life. April 12/13th 2013, 2013)
The process of general and specific training and of competition activity specific to handball game requires the players to possess a high level of coordinative capacity, which allows efficient adaptation of technical and tactical possibilities to the practical developing conditions of games. The research was carried out in December 2011, on a number of 20 subjects, practicing handball, with ages between 16-18 years; 10 of them with right manual dominance and other 10 with left manual motion prevalence and had in view to identify the general coordination level according to laterality with the help of Matorin test. The average score of the females at the test on the right side was 8.3 for those with right laterality and 7.4 for those with left laterality. At the test on the left side the average score was: 7.8 for those with right laterality and 8.7 for those with left laterality. In what the males are concerned, the test results for the right-handers were 8.2 points at the test on the right side and 7.3 points on the left, as for those with left laterality, the score was 7.3 for execution on the right and 8.4 for the left side. The results confirmed the hypothesis from which we started the research and show the fact that the general coordination level is directly influenced by laterality and inferentially by the motion prevalence. The left-handers` results both of the females and males were slightly better than those of the right-handers.